PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR AGRO CIPTA ADIGUNA PARE (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2018)
Effective saving style can be used as an example and good example for members or people who are led and able to motivate to achieve the goals of the company employees of PT BPR Agro Cipta Adiguna Pare. The method of analyzing this research data is Multiple Linear Regression Test, Classical Assumption Test, and / or Hypothesis Test. The results of this study Leadership Style (X1) on the positive so significant effect on Employee Performance the results of the test t the value is significant 0.003, in the Work Environment (X2) positively or significantly affected the Employee Performance the results t test value is significant His leadership style and work environment are simultaneously positively and significantly affected by Employee Performance as seen from the results of the F Test with sig values (0,000